Antecedents and Consequences of Individual Market Orientation - Baber, Ruturaj; Upadhyay, Yogesh; Kaurav, Rahul Pratap Singh (Prabandhan: Indian Journal of Management, 2015)
Even if evaluated at an organizational level, a market-oriented culture of an organization is genuinely supported by the outlooks and activities of the organization's employees. A market orientation strategy cannot be developed without every employee's active understanding, willingness, and ability to perform in market-oriented methods. Consequently, an individual employee must be familiar with the task of gathering and assessing the value of market information, and also, he should be willing to share it with other employees. We surveyed a variety of employees at many levels and roles in different central Indian financial services organizations. This research identifies the important individual-level antecedents and consequences that organizations should account for once making an attempt to stimulate company-wide market-oriented behaviours. These embrace the fostering psychological contracts, modelling of learning methods by agile learners, inflated opportunities, and time to develop personal ties between customers and workers in numerous roles at intervals in the firm.